Implementasi Kode Etik Guru Dalam Meningkatkan Mutu Pendidikan Melalui Strategi Dan Prinsip – Prinsip Profesionalisme di Lembaga Pendidikan Islam - Muhammad Zaidan; Astuti Darmiyanti; Saprialman Saprialman (Peneliti.net, 2023)
This study aims to determine the implementation of the teacher's code of ethics in improving the quality of education through strategies and principles of professionalism in Islamic educational institutions. This study uses a qualitative method with a descriptive approach. Data obtained through observation, interviews, and documentation. The results of the study show that the implementation of the teacher's code of ethics in Islamic education institutions has been carried out well, but there are still some obstacles in its implementation. These obstacles include the lack of socialization regarding the teacher's code of ethics to teachers, the teacher's lack of understanding of the teacher's code of ethics, and the lack of sanctions given to teachers who violate the code of ethics. To improve the quality of education, Islamic educational institutions implement strategies and principles of professionalism, namely increasing teacher competence through training and seminars, applying innovative learning methods, and developing a quality evaluation system. From the results of this study, it is suggested to Islamic education institutions to further increase socialization regarding the teacher's code of ethics, increase teachers' understanding of the code of ethics, and provide strict sanctions to teachers who violate the code of ethics. In addition, Islamic educational institutions must also continue to improve strategies and principles of professionalism to improve the quality of education.